Analisis efisiensi usahatani padi organik pada kelompok tani Paguyuban Bumi Mandiri di Desa Pringkasap Kecamatan Pabuaran Kabupaten Subang Jawa Barat - Wendi Juliawan; Yayah Haeriah; Edeng Edeng; Asep Najmudin; Vega Chendra Mulyana (University of Insan Cendekia Mandiri, 2024)
Organic rice production can be a solution for food and environmental security. In this context, farmers who are members of the Paguyuban Bumi Mandiri Farmers Group have been implementing organic rice cultivation since 2021 under the guidance of CV. Agrospora. The method used in this research is a descriptive survey. The descriptive method is a method used to describe or analyze research results but is not used to make broader conclusions. The objects of this research are farmers who are members of the Paguyuban Bumi Mandiri farmer group in Pringkasap Village, Pabuaran District, Subang Regency, West Java. Sampling was carried out using the simple random sampling method. 13 samples from a total population of 22 members of farmer groups. The data collected consists of primary data and secondary data. To determine the efficiency of organic rice farming, it is analyzed using the R/C Ratio and Break Event Point analysis. The R/C Ratio efficiency analysis shows a value of 2.4, which is greater than 1. This means that economically the Organic Rice farming in the Paguyuban Bumi Mandiri farmer group is efficient. The BEP calculation produces a Production BEP of 987.8 kg and a price BEP of Rp. 2,700